MANAJEMEN PENDIDIKAN BERBASIS FUTURE SKILLS DI SEKOLAH DASAR - Widiansyah, Apriyanti; Fitriansyah, Fifit; Saputra, Rahmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the challenges of 21st-century education, which require elementary schools to develop students’ future skills, such as critical thinking, creativity, collaboration, communication, digital literacy, and adaptability. However, the implementation of educational management in elementary schools still tends to focus on conventional academic achievement, resulting in the suboptimal development of future skills. This study aims to analyze the implementation of future skills-based educational management in elementary schools, including the planning, implementation, and evaluation of learning programs that support students’ future competencies. This research employed a qualitative approach using a case study method in several elementary schools implementing 21st-century skills-based learning. Data were collected through interviews, observations, and documentation studies. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that future skills-based educational management can improve the quality of learning through the integration of digital technology, the implementation of project-based learning, literacy enhancement, and collaboration among schools, teachers, and parents. In addition, schools implementing future skills-based management are able to create a more innovative, adaptive, and student-centered learning environment. The challenges identified include limited teachers’ digital competencies and inadequate learning support facilities. Therefore, strengthening teacher training and school policy support is necessary to ensure the sustainable implementation of future skills in elementary schools